2022
DOI: 10.56093/ijas.v92i8.90437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of growth, yield and yield attributing traits in sugarcane (Saccharum officinarum) under different soil moisture regimes

Abstract: A field experiment was conducted during spring season of 2014–15 and 2015–16 at CCS HAU, RRS, Karnal to evaluate the response of four sugarcane (Saccharum officinarum L.) varieties differing in their maturity i.e. CoS 767 (Mid late), CoH128 (Mid late), CoJ 64 (Early) and Co 0238 (Early) to deficit irrigation. The experiment was conducted in split plot design with three replications. Based on available soil moisture (ASM), three treatments i.e. irrigation at 50% ASM (control), 40% ASM (mild stress) and 30% ASM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…This revealed that the mid‐season stage is the most important stage for yield formation in sugarcane and that extreme water deficit is intolerable during this stage. These results are quite similar to those of Dhansu et al (2022), who found that soil moisture has a positive effect on cane girth.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This revealed that the mid‐season stage is the most important stage for yield formation in sugarcane and that extreme water deficit is intolerable during this stage. These results are quite similar to those of Dhansu et al (2022), who found that soil moisture has a positive effect on cane girth.…”
Section: Resultssupporting
confidence: 92%
“…It is possible to establish irrigation scheduling recommendations based on crop sensitivity to water deficit for different growth stages in order to meet water requirements during deficit‐sensitive growth stages when imposing deficits during less deficit‐sensitive stages. To establish an effective DI scheduling for sugarcane, various studies have been conducted in many growing regions around the world (Dhansu et al, 2022; Dinh et al, 2017; Ellis & Lankford, 1990; Hoang et al, 2018; Inman‐Bamber & Smith, 2005; Ishaq & Olaoye, 2009; Olivier & Singels, 2012; Ramesh & Mahadevaswamy, 2000; Robertson et al, 1999; Santos et al, 2019; Singh & Mohan, 1994; Singh et al, 2007, 2018; Sudhakar et al, 2010; Wagih et al, 2003; Wiedenfeld, 2000; Zhao et al, 2013). These studies show that, when managed properly, DI would increase water efficiency while retaining sugarcane yields and quality at economically reasonable levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation